2011
DOI: 10.1186/1751-0147-53-56
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and genetic diversity of Enterococcus faecalis among layer chickens during hatch

Abstract: BackgroundStudies on transmission of Enterococcus faecalis among chickens during hatch have not been carried out so far. Information about vertical transmission and subsequent spreading and colonization of the cloacal mucosa through cloacal 'drinking' during hatch are important to understand the epidemiology of E. faecalis infections. In the present investigation vertical transmission and subsequent spreading and colonization of the cloacal mucosa of chickens by E. faecalis through cloacal 'drinking' were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…In studies carried out in other countries, E. faecalis was also the predominant Enterococcus species in faecal samples from poultry (Yoshimura et al, 2000;Kuhn et al, 2003;Poeta et al, 2006). According to the literature, chickens are initially colonised by E. faecalis (Fertner et al, 2011), but this population is then displaced, mainly by E. faecium (Kaukas et al, 1987). In this study, the dominance of E. faecalis could be linked to the age of the birds tested.…”
Section: Discussionmentioning
confidence: 72%
“…In studies carried out in other countries, E. faecalis was also the predominant Enterococcus species in faecal samples from poultry (Yoshimura et al, 2000;Kuhn et al, 2003;Poeta et al, 2006). According to the literature, chickens are initially colonised by E. faecalis (Fertner et al, 2011), but this population is then displaced, mainly by E. faecium (Kaukas et al, 1987). In this study, the dominance of E. faecalis could be linked to the age of the birds tested.…”
Section: Discussionmentioning
confidence: 72%
“…, ,b; Fertner et al . ; Thayer and Waltman ). Enterococcus faecalis affects avian species of all ages; however, the majority of serious infections have been associated with embryos and young birds (Fertner et al .…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus faecalis affects avian species of all ages; however, the majority of serious infections have been associated with embryos and young birds (Fertner et al . ; Olsen et al . , ,b; Thayer and Waltman ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical conditions observed in poultry include pulmonary hypertension syndrome [3], and amyloid arthropathy [4], in addition to first week mortality [2]. Also, a study has demonstrated the high potential of a few E. faecalis -contaminated eggs or embryos to rapidly facilitate the spread of this bacterium to almost all chickens during hatch [5]. More recently, it was demonstrated that E. faecalis of human and poultry origin shared virulence genes supporting the zoonotic potential of E. faecalis [6].…”
Section: Introductionmentioning
confidence: 99%